2021
DOI: 10.3390/nano11123213
|View full text |Cite
|
Sign up to set email alerts
|

Recent Development in Vanadium Pentoxide and Carbon Hybrid Active Materials for Energy Storage Devices

Abstract: With the increasing energy demand for portable electronics, electric vehicles, and green energy storage solutions, the development of high-performance supercapacitors has been at the forefront of energy storage and conversion research. In the past decade, many scientific publications have been dedicated to designing hybrid electrode materials composed of vanadium pentoxide (V2O5) and carbon nanomaterials to bridge the gap in energy and power of traditional batteries and capacitors. V2O5 is a promising electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 137 publications
0
7
0
Order By: Relevance
“…As we generate more energy from renewable sources, such as solar [ 5 ], hydroelectric [ 6 ], thermoelectric [ 7 ], and microbial [ 8 ], we require high capacity that can store excess energy in low demand and release the stored energy on demand. Thus, there is growing interest in next-generation energy storage technologies like supercapacitors [ 9 ], sodium-ion batteries [ 10 ], and solid-state batteries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…As we generate more energy from renewable sources, such as solar [ 5 ], hydroelectric [ 6 ], thermoelectric [ 7 ], and microbial [ 8 ], we require high capacity that can store excess energy in low demand and release the stored energy on demand. Thus, there is growing interest in next-generation energy storage technologies like supercapacitors [ 9 ], sodium-ion batteries [ 10 ], and solid-state batteries [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Such composites with superior surface morphology exhibit improved electrochemical performance. Recent studies report that the increased specific surface area of such nanocomposites drastically affects the specific capacitance , as well as the power density. In addition, the proper choice of a suitable electrolyte plays an important role in supercapacitor applications.…”
Section: Introductionmentioning
confidence: 99%
“…28 In general, SC electrodes made with CNTs and V 2 O 5 have capacitance values of 100-630 F g À1 , but their energy densities are below 100 W h kg À1 . 29,30 More importantly, their discharge times are short (maximum 1000 s). Moreover, solid state devices made with CNTs, and vanadium oxides have been scarcely reported: Chen et al 31 reported a symmetric SC made with CNT/V 2 O 5 electrodes, which provided a capacitance/ energy-density of 115 F g À1 /40 W h kg À1 .…”
Section: Introductionmentioning
confidence: 99%